2022
DOI: 10.3892/mco.2022.2557
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal presentation of a bilateral, synchronous and plurimetastatic medium and large cell testicular lymphoma: A case report

Abstract: Primary testicular lymphoma (PTL) accounts for 1-2% of all cases of non-Hodgkin's lymphoma, with a higher incidence in patients aged >60 years. The most common histological subtype is diffuse large-cell B lymphoma. By contrast, the bilateral synchronous and multimetastatic clinical presentation is a rare and unusual clinical presentation. In testicular masses, orchiectomy is essential for histopathological evaluation of the disease and definition of the immunophenotypic structure. The present study reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although other extranodal sites of relapse reportedly include Waldeyer’s ring and the skin, no report has described relapse in the glans penis [ 1 , 3 , 4 , 6 ]. A rare case of bilateral synchronous testicular involvement of PTL was recently reported, but the spermatic cord and glans penis were intact by surgical examination [ 18 ]. Also in our patient, no infiltration of the spermatic cord by surgical examination at initial high orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although other extranodal sites of relapse reportedly include Waldeyer’s ring and the skin, no report has described relapse in the glans penis [ 1 , 3 , 4 , 6 ]. A rare case of bilateral synchronous testicular involvement of PTL was recently reported, but the spermatic cord and glans penis were intact by surgical examination [ 18 ]. Also in our patient, no infiltration of the spermatic cord by surgical examination at initial high orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, testicular cancer is rare before age 15 [44]. Regarding testicular cancer in older men (>50 years), it has to be reported, however, that the most commonly occurring testicular malignancy is testicular lymphoma, often secondary to non-Hodgkin lymphoma, while the primary testicular lymphoma is rare and could have a different age range [45][46][47].…”
Section: Agementioning
confidence: 99%
“…It is also clinically important to identify biomarkers that can predict the effectiveness of genotoxic drugs, so as to avoid exposing nonresponders to potentially harmful treatments. A study utilizing a whole-genome CRISPR/Cas9 gene knockout approach identified ASH2L, a core component of the H3K4 methyl transferase complex, as a protein necessary for bleomycin sensitivity in Hodgkin lymphoma [104]. ASH2L levels could potentially serve as a biomarker for predicting the response to genotoxic drugs in testicular cancer.…”
Section: Non-common Testicular Cancers and Possible Epigenetic Biomar...mentioning
confidence: 99%
“…ASH2L levels could potentially serve as a biomarker for predicting the response to genotoxic drugs in testicular cancer. In cases where tumors express low levels of ASH2L, which may confer resistance to genotoxic treatment, the use of ATR or ATM inhibitors might be more effective, as data suggest that ASH2L knockdown does not affect sensitivity to these inhibitors [104].…”
Section: Non-common Testicular Cancers and Possible Epigenetic Biomar...mentioning
confidence: 99%